Blazer and Ashland Oil : a study in management - Massie, Joseph L. (The University Press of Kentucky, 1960)
Tracing the evolution of the Ashland Oil & Refining Company whose growth was phenomenal even in a rapidly expanding industry, author Joseph L. Massie attributes the success of the company to the flexible management policies of Paul G. Blazer.